Influence of Chitosan and Alginate as Reinforcement Towards Sugar Palm Starch-Based Hydrogel - Zahra, Tazkia Qonita; Nizardo, Noverra Mardhatillah; Restu, Witta Kartika (Universitas Jenderal Soedirman, 2024)
Nowadays, hydrogel has a wide range of applications, such as in the biomedical field, due to its excellent biocompatibility. Hydrogel may be synthesized using biomaterials that are abundantly found in the natural environment. This research involved the synthesis of a hydrogel using sugar palm starch as the base material, but hydrogel made from starch has lower chemical and physical properties. To enhance its chemical, physical, and mechanical properties, alginate and chitosan were incorporated as reinforcing agents because they can form strong gels, which might be due to the interaction of the amino (-NH2) group from chitosan and carboxyl (-COO-) group from alginate with the hydroxyl (-OH) group from starch. The objective of the study was to determine the best reinforcing agents for the formation of two sugar palm-based hydrogel formulations: sugar palm starch/chitosan hydrogel and sugar palm starch/alginate hydrogel, with good chemical, physical and mechanical properties, such as thickness, swelling ratio, water contact angle, functional group, mechanical properties including tensile strength, and elongation at break, surface morphology images, and thermal properties. The result showed that the hydrogel composed of sugar palm starch and chitosan as reinforcing agent exhibited better characteristics than alginate, indicating their potential for biomedical application as shown by its result in swelling ratio with value of 67.81±0.11%, average tensile strength of 0.113±0.04 MPa and elongation at a break value of 37.83±7.0%. Keywords: Alginate, chitosan, hydrogel, Sugar palm starch